Quantity and biochemical composition of sedimentary organic matter around offshore gas extraction platforms of the Adriatic Sea. Issue 1 (2nd January 2017) - Punzo, E.; Bianchelli, S.; Pusceddu, A.; Salvalaggio, V.; Santelli, A.; Strafella, P.; Fabi, G.
ABSTRACT: Gas platforms can exert relevant effects on various ecosystem properties of the hosting area, modifying patterns of productivity and particle sedimentation. We hypothesised that the presence of gas platforms is associated with higher organic matter (OM) contents and we tested the null hypothesis by which benthic trophic conditions do not vary significantly among gas structures with different architectural characteristics. To test these hypotheses, we investigated sedimentary OM contents and biochemical composition at increasing distance from two distinct structures: one subsea well-site and one four-leg platform (FLP). We found that sediments surrounding the structures were characterised by similar OM contents, but different biochemical compositions, and that sedimentary OM compositional change with increasing distance from the structure is confirmed only at the FLP. These results suggest that: (i) benthic eutrophication is not consistent among different structures; (ii) OM biochemical composition changes are more evident than those in OM quantity; and (iii) the effect, wherever present, disappears at a very narrow distance from the platform. As biochemical composition of OM reflects food availability for benthic organisms, our results suggest that the enrichment of macrozoobenthic communities around these structures could be the consequence of increased nutritional quality of resources.